OP0189 Identification of new and rare variants in abcg2, slc22a1 and aldh16a1 genes in crystal-proven early-onset gout. (12th June 2018) - Collet, C.; Morel, H.; Ricquebourg, M.; Cohen-Solal, M.; Laplanche, J.-L.; Pascart, T.; Bardin, T.; Lioté, F.; Richette, P.; Ea, H.K.
Abstract : Background: Early-onset or juvenile gout (EOG) without hypoxanthine-guanine phosphoribosyltransferase enzyme deficiency ( HPRT, OMIM 300323) and not related to familial juvenile hyperuricemic nephropathy ( UMOD, OMIM 300323) is a rare gout phenotype characterised by a first flare in adolescence or in young adulthood. While numerous genome wide association studies (GWAS) have been done in classical and late-onset gout, very few studies have been performed in EOG patients. Moreover, until now most genetic studies only assess association between pre-defined single nucleotide polymorphisms (SNP) and gout. Objectives: Our aim was to identify the genetic variants of clinically confirmed EOG by screening all exons of gout-associated genes with targeted Next-Generation Sequencing (NGS) approach. Methods: Twenty-six urate crystal-proven gout patients with first flare occurring before the age of 30 years were included. Gout history, comorbidities and patient characteristics were recorded. All participants provided written informed consent to genetic analysis. After DNA extraction from total blood samples, the NGS libraries were prepared with surselect QXT (Agilent) and sequencing was performed with miseq (Illumina). The multigene panel included 80 genes described in GWAS and genes involved in rare diseases such as HPRT and UMOD . Results: Twenty-six patients (24 men, 20 Caucasians, 5 Asians and 1 African) with crystal-proven gout had experienced their first flare at a mean age of 22.8 years [14–29] Gout duration was 11.5 years [1–46] and clinical tophi observed in 9 patients. Mean age was 37.5 [24–69] years and mean body mass index 27.6 kg/m2 [20.1–40.7]. Ten patients were overweight, 5 had obesity, 1 hypertension, 0 diabetes mellitus, 7 dyslipidemia and 10 chronic kidney disease stages 2–4. Mean serum urate level was 527 µmol/L [270–803]. Amongst 26 affected patients, 7 had a molecular anomaly (26.9%). Six patients harboured one rare or novel variant in ABCG2 (three Caucasian patients), ALDH16A1 (two Caucasian patients) and SLC22A11 (one African patient). Two other patients (one Caucasian and one Asian) carried an association of variants in both ABCG2 and ALDH16A1 . All variants had a Minor Allele Frequency (MAF) below 0.3% or were never described in public databases. All variant were considered as probably pathogenic according to in silico predictive algorithms. Interestingly, the well-known p.Gln141Lys SNP of ABCG2 was identified in 3 Asian patients (11.5%) at homozygous level. Conclusions: Our finding of very rare and novel pathogenic variants in ABCG2, ALD16H1 and SLC22A11 genes provides better insights of the molecular pathogenesis in early-onset juvenile gout. However, our results also highlight the involvement of yet undetermined genes in this population. Disclosure of Interest: None declared